Estudo da sedimentação de partículas em fluidos de perfuração pelo usa da técnica de atenuação de raios gama - Fagundes, Flávia Marques (2019)
The development of techniques to make safer oil well drilling processes is under constant review. During drilling, there are different types of rock formations, requiring fluids of different formulations for each drilled level. The fluid, when pumped into the well, has as one of its functions to carry the particles generated by the drill to the surface, for later cleaning and reinjection of fluid in the system. Besides, it should contribute to the maintenance of suspended particles in situations of operational shutdowns or confinement of drilling fluid. Therefore, suspensions with pseudoplastic and thixotropic rheological characteristics are formulated. However, sedimentation is inevitable. Concerning this scenario, this work had as objectives to evaluate the settling in fluids of different degrees of shear-thinning and thixotropy and also to propose constitutive equations for pressure on solids and the calculation of the permeability. For this purpose, fluids of different concentrations of carboxymethyl cellulose (0.2, 0.4, 0.6, 0.8 and 1.0% w/w) and hematite weighting (12.7, 16.9, 24.6 and 31%) were rheologically characterized and the particles settling was studied through the Gamma Ray Attenuation Technique (TARG). This non-destructive technique allowed the indirect monitoring of the volumetric concentration of solids in long periods of sedimentation experiments. Thus, both the rheological behavior and the settling monitoring showed that the carboxymethyl cellulose polymer (CMC) concentration or the hematite addition contributed to the process of maintaining the particles suspended in the fluids. Also, the hypothesis of pressure on solids only depends on the concentration of particles was confirmed; and a proposal of the equation for the sediment permeability was presented based on the equation of motion and the particle settling velocity in non-Newtonian fluid, proposed by Laruccia (1990). Regarding the permeability value, it was noticed that the final accommodation of solid sediment in CMC fluids was the factor that most contributed to the values found.